Compliance of hot work permit to process safety management (PSM) regulation - Majid, N.D.A. (Trans Tech Publications Ltd, 2014)
Work permit is something not to take lightly because it involved non-routine work such as hot work which failure to comply with the work permit procedures could resulted in large-scale loss of life and/or property. Investigations by Chemical Safety Board (CSB) have reported 60 fatal hot work accidents in about 20 years in the USA though hot work permits were issued for all operations. No matter how simple the procedure and work permit forms are, it is the strict application of the procedures and practices associated with the assessment of risk and application of permit to work conditions that ensures work can be done safely. A model for hot work permit that is incompliance with the Process Safety Management (PSM) regulations requirements is introduced that includes necessary fire preventive actions to be taken. In addition, a few existing hot work permits were studied to verify this model. It was found that the model required more information to safeguard an effective hot work permit system and better compliance with the PSM regulation. In addition, the model is also more precise, adaptable, user-friendly and easier to comprehend. As a conclusion, the model created could improve the conventional hot work permitting system. To ensure that the permit is more strict and effective hot work permitting system, a more sophisticated coding and software could be further expanded. Â© 2014 Trans Tech Publications, Switzerland.